Scope and Limitations of Current Antibiotic Therapies against Helicobacter pylori: Reviewing Amoxicillin Gastroretentive Formulations - Roberto Grosso; M.-Viola (MDPI AG, 2022)
Even though general improvement of quality of life has happened around the globe, statistics show that gastric cancer is still a very serious medical concern in some regions of the world. A big portion of malignant neoplasms that develop inside the stomach are linked to an infection of Helicobacter pylori; in fact, this pathogen has already been categorized as a group 1 carcinogen by the World Health Organization (WHO). Still, the efficacy of current anti-H. pylori therapeutic approaches is insufficient and follows a worrying decreasing trend, mainly due to an exponential increase in resistance to key antibiotics. This work analyzes the clinical and biological characteristics of this pathogen, especially its link to gastric cancer, and provides a comprehensive review of current formulation trends for H. pylori eradication. Research effort has focused both on the discovery of new combinations of chemicals that function as optimized antibiotic regimens, and on the preparation of gastroretentive drug delivery systems (GRDDSs) to improve overall pharmacokinetics. Regarding the last topic, this review aims to summarize the latest trend in amoxicillin-loaded GRDDS, since this is the antibiotic that has shown the least bacterial resistance worldwide. It is expected that the current work could provide some insight into the importance of innovative options to combat this microorganism. Therefore, this review can inspire new research strategies in the development of efficient formulations for the treatment of this infection and the consequent prevention of gastric cancer.